Recent developments of a co-immobilized laccase–mediator system: a review. Issue 47 (2nd September 2021) - Gu, Yaohua; Yuan, Lin; Jia, Leina; Xue, Ping; Yao, Huiqin
Abstract : The laccase–mediator is a promising biocatalyst with many possible applications, including bioremediation, chemical synthesis, biobleaching of paper pulp, biosensing, textile finishing and wine stabilization. Abstract : The laccase–mediator is a promising biocatalyst with many possible applications, including bioremediation, chemical synthesis, biobleaching of paper pulp, biosensing, textile finishing and wine stabilization. The immobilization of laccase and the mediator offers several improvements for laccase–mediator system applications because the storage and operational stabilities are frequently enhanced. Moreover, the reusability of the immobilized laccase and mediator represents a great advantage compared with the free laccase and mediator. In this work, we review the methods of co-immobilization of the laccase–mediator system for the first time systematically and comprehensively. In addition, we discuss the different methodologies of laccase and mediator immobilization that have been reported.